Parque Eco-educativo de Minas y Energías Medio Magdalena: Plan parcial tejidos vitales el silencio (2017)
Based on the proposal of a partial plan that responds to the parameters and characteristics of the environment, being Bucaramanga-Girón-Barrancabermeja the corridor to study, their vocations and needs are investigated to justify a planned development in this place. After the approval of the Partial Plan, an Action Unit is chosen to optimize the execution of specific projects. That is why an Ecological Park focused on extraction education is proposed, to help expanding the local knowledge in areas that are not alien to them since it is what is produced in their environment, involving them in the commercial chain and therefore improving their quality of life.